2013
DOI: 10.4187/respcare.02364
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin Kinetics and Nosocomial Pneumonia in Older Patients

Abstract: BACKGROUND: Early identification of treatment failure for nosocomial pneumonia remains a major challenge. The goal of this study was to test whether procalcitonin kinetics can be used to assess the clinical efficacy in older critically ill patients with nosocomial pneumonia. METHODS: A prospective observational study was conducted with 60 subjects (> 65 y old) admitted to the ICU with severe nosocomial pneumonia. Serum procalcitonin was measured on days 0, 3, and 7 and at the end of treatment. The procalcitoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
14
1
Order By: Relevance
“…While some investigators reported usefulness of PCT for diagnosing bacterial infection in the elderly [8, 11, 47], others revealed that PCT was inferior to CRP for predicting bacterial infection in these population [9, 48, 49]. As for predicting capacity for clinical course, Shi et al reported that there were no differences in PCT between the improved and not-improved subjects in nosocomial pneumonia in the elderly [50]. To our knowledge, this is the first study to examine the relationship between PCT levels by pneumonia severity in younger and elderly patients with pneumonia, particularly patients with S. pneumoniae pneumonia, occurring outside the hospital setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some investigators reported usefulness of PCT for diagnosing bacterial infection in the elderly [8, 11, 47], others revealed that PCT was inferior to CRP for predicting bacterial infection in these population [9, 48, 49]. As for predicting capacity for clinical course, Shi et al reported that there were no differences in PCT between the improved and not-improved subjects in nosocomial pneumonia in the elderly [50]. To our knowledge, this is the first study to examine the relationship between PCT levels by pneumonia severity in younger and elderly patients with pneumonia, particularly patients with S. pneumoniae pneumonia, occurring outside the hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to examine the relationship between PCT levels by pneumonia severity in younger and elderly patients with pneumonia, particularly patients with S. pneumoniae pneumonia, occurring outside the hospital setting. In addition, the present study included more elderly patients than those that previously assessed the clinical usefulness of PCT in the elderly population [811, 4750]. We assessed the relationship between PCT and PSI, because mortality in this frail elderly population is frequently not directly due to pneumonia [51], and PSI could be more specific of pneumonia severity than all cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CAP, we investigated the role of PCT in patients with HCAP, a group with limited investigation in this field [30, 31]. It is interesting to note that there was no significant difference between PCT values for patients with CAP and HCAP.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study involving 60 older patients with nosocomial pneumonia who were admitted to the ICU, the evaluation of PCT kinetics between the time of admission and the third day of follow-up was the best single predictor of therapeutic efficacy, with an AUC of 0.79 (p < 0.001). ( 38 ) Similarly, a study from 2006 evaluated the prognostic value of PCT kinetics in patients with CAP who were admitted to the ICU; the study indicated favorable results. ( 39 ) One hundred patients were included, and serum PCT levels were measured on days 1 and 3.…”
Section: Prognostic Value Of Procalcitonin In Lower Respiratory Tractmentioning
confidence: 99%